Pengaruh Kemisikinan Terhadap Akses Pendidikan Bagi Anak Nelayan di Aceh Selatan - Wini Delvia Riski; Vellayati Hajad (Jurnal Public Policy, 2021)
The aim of this study is to analyze the impact of poverty on access to education for fishermen's children in the South Aceh District. Poverty is a condition that causes a person to be unable to enjoy health, higher education and to consume adequate food from a health perspective. As a result, they have low productivity, decent work and low incomes. The method used is quantitatively explained by the creation of 18 fishermen in Ujung Tanah Village, Samadua District, South Aceh Regency.Data was obtained through questionnaires and interviews and analyzed through a Spearman correlation test using the IBM SPSS Statistics Version 20 software to test the influence between variables and explain the relationship between the two. Research data shows that at SD level p >0.05, SMP p>0.05, SMA p>0.005, S1 p>0.005. In the meantime, the value of the correlation test is -0.252 (SD), -0.258 (SMP), -0.140 (SMA), -0.129 (S1). The conclusion is, therefore, that the hypothesis (Ho) is accepted, that is, that there is an influence between poverty (X) and education (Y) on the children of fishermen with a negative or opposite correlation. Namely, the higher the poverty, the lower the education of the children of fishermen.